(untitled) (Contemporary Mathematics, 2024)
The purpose of this study is to investigate the effects of radiation and activation energy on mass transfer nanofluids flowing across an expanding sheet in a vertical direction, as well as joule heating, viscous dissipation, Soret and Dufour, and magnetohydrodynamic (MHD) flow. The boundary layer (BL) equations for nonlinear momentum, energy, solute, and nanoparticle volume fraction are reduced by using similarity transformations. After that, the shooting technique and bvp4c are used to numerically solve the boundary layer equations. Schmidt and Eckert’s numbers, along with Soret effects on velocity, temperature, and the volume percentage of nanoparticles, cause an increase in skin friction. Fluid temperature rises significantly with Eckert number. As the Dufour and Schmidt numbers rise, so does the local Nusselt number. A greater thermophoresis parameter, enhanced skin friction, and an increased Schmidt number.